MEMAKNAI SUMPAH PEMUDA DI ERA REFORMASI - Widodo, Sutejo K. (HUMANIKA, 2012)
The moment of Sumpah Pemuda (Young Man Oath) took place 84 years ago, reflecting the spirit of nationalism that is still very important in this Reformation era. This paper endeavors to dig deeper meaning of Sumpah Pemuda in its pre-independence era and applying it to our contemporary situation. The method used here is historical research using literature resources, such as articles, books, and other readings in internet. It is then concluded that the spirit of Sumpah Pemuda should be our contemplative materials and valuable Iesson so that Reformation era may succeed in achieving national goals stated in the Constitution, a society that is fair, prosperous, and democratic. Keywords: Sumpah Pemuda, Reformation era, nationalism.